2013
DOI: 10.7241/ourd.20132.36
|View full text |Cite
|
Sign up to set email alerts
|

A study on tinea capitis in the pre school and school going children

Abstract: Introduction: Tinea capitis is a superficial fungal infection of scalp and hair caused by various species of dermatophytes. The incidence of Tinea capitis varies from country to country and region to region. Material and Methods: Fifty patients from the preschool going population were selected for the study. Results and Discussion: Clinical presentation of disease revealed that black dot to be the commonest (32%) followed by grey patch (28%), kerion (20%) and favus type was the least (1%). Direct microscopy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Tineas are mainly caused by antrophophilic or zoophilic dermatophytes worldwide, such as T. rubrum and M. canis, however, geophilic fungi have a more extended geographic distribution such as Microsporum gypseum [4] which is the most important soil acquired pathogen but clinical cases due to this agent are scarce. This causative agent can affect cats, dogs, rodents and horses, and in humans, in some cases, it can cause tinea corporis, tinea capitis and tinea faciei [5].…”
Section: Discussionmentioning
confidence: 99%
“…Tineas are mainly caused by antrophophilic or zoophilic dermatophytes worldwide, such as T. rubrum and M. canis, however, geophilic fungi have a more extended geographic distribution such as Microsporum gypseum [4] which is the most important soil acquired pathogen but clinical cases due to this agent are scarce. This causative agent can affect cats, dogs, rodents and horses, and in humans, in some cases, it can cause tinea corporis, tinea capitis and tinea faciei [5].…”
Section: Discussionmentioning
confidence: 99%
“…Nail changes in psoriasis include pitting (small, regularly placed pits, as on a thimble) ( Fig. 7) [16][17][18].…”
Section: Thimble Signmentioning
confidence: 99%
“…For instance, Mahmoudabadi et al [20], Rasi et al [21] and He et al [22] found that more males were affected with versicolor infection than women in Iran and China respectively. However, among children, the most common dermatophyte infection is Tinea capitis [6].…”
Section: Gender and Skin Infectionmentioning
confidence: 99%
“…In year 2010, out of 14 048 cases, treated at the dermatology specialist clinics, highest percentage of skin infections were of fungal origin (12.4%) and the lowest percentage of (3.6%) were of bacterial sources as compared to the year 2011, where 12.7% of skin infections were of fungal origin and 3.4% of bacterial origin [2]. Numerous factors can contribute to the development of skin infection such as: poor skin health, low socioeconomic status, low level of hygiene, overcrowding and also lack of awareness [3][4][5][6]. In Tigray (Northern Ethiopia), eczema was most common and acne the least common among the outpatient attendance and a positive correlation between these skin infections with factors such as overcrowding, poor hygiene and low socioeconomic status was reported [7].…”
Section: Introductionmentioning
confidence: 99%